On the size of sheepskin effects: A meta-analysis - Jhon James Mora Rodríguez; Juan Muro (Kiel Institute for the World Economy (IfW), 2015)
The authors use information gathered from 122 studies on the effects of high school diplomas on wages in different countries worldwide to carry out a meta-analysis that shows high school diplomas have a statistically significant effect on wages of nearly 8 percent. This effect varies whether the country is away from the tropics or whether factors such as sex, race, and continent are taken into account. The authors' results also reveal the existence of a publication bias that tends to increase the magnitude of the sheepskin effect. Nevertheless, when the former is factored into the analysis the latter remains statistically significant.
Keywords: C8; I21; J24; 330; Sheepskin effects; meta-analysis; publication bias